EFFECTIVENESS OF STEM-BASED DISCOVERY LEARNING MODEL TO IMPROVE CRITICAL THINKING SKILLS OF JUNIOR HIGH SCHOOL STUDENTS - Widdya Asmara Dewi; Nurma Yunita Indriyanti; Icha Kurnia Wati (NUKLEO SAINS : JURNAL PENDIDIKAN IPA, 2025)
This research aims to (1) to determine the effectiveness of the discovery learning model based on the STEM approach on the critical thinking skills of junior high school students in grade VII on the Solar System material, and (2) to analyze the discovery learning model based on the STEM approach in improving the critical thinking skills of junior high school students. The design of this study uses mixed methods simultaneously. The discovery learning model Based on the STEM Approach is applied to the experimental class and the discovery learning model is applied to the control class. Data collection was carried out by critical thinking skills tests and non-tests in the form of observations and interviews. The data analysis technique used in this study uses normality and homogeneity tests. The hypothesis was tested using an independent sample t test using N-Gain%.  The results showed that there was a difference in the average increase in the pretest and posttest scores of students' critical thinking skills in the Solar System material by using the N-Gain% test in the control class by 18.69% and the experimental class by 34.47%. From the results of the independent t-test hypothesis test using NGain% with the help of the SPSS 32 application, the value of sig 2 tailed was obtained as 0.003 <0.05 and t calculated > t table (3.063 > 2.988), then it can be decided that H1 is accepted. Therefore, it can be concluded that the discovery learning model based on the STEM approach has a positive effect on improving the critical thinking skills of junior high school students.